Third Grade Achievement Predictors in Urban Poverty Settings: End of Kindergarten Behavioral and Performance Indicators - Gullo , Dominic F.; Ammar, Alia A. (Journal of Social Science Studies, 2021)
Structural equation modeling was used to investigate the predictive associations between end of kindergarten academic, social behavioral, and biotic influences on end of third grade academic achievement among a nationally representative sample of low-socioeconomic (SES) children residing in urban areas. Findings validate the understanding that developmental and learning trajectories start early and are influenced by multifaceted factors. Understanding factors that positively and negatively affect learning and development among urban low-SES children informs intervention strategies potentially moderating the gaps that exist in these areas among SES groups.